Upscaling of Bio-Nano-Processes Selective Bioseparation by Magnetic Particles - Nirschl, Hermann; Keller, Karsten; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Despite ongoing progress in nano- and biomaterial sciences, large scale bioprocessing of nanoparticles remains a great challenge, especially because of the difficulties in removing unwanted elements during processing in food, pharmaceutical and feed industry at production level. This book presents magnetic nanoparticles and a novel technology for the upscaling of protein separation. The results come from the EU Project "MagPro2Life", which was conducted in cooperation of several european institutions and companies.
Introduction -- Part I: Particle Synthesis and Functionalization -- New Advances in the Production of Iron-Based Nanostructures by Laser Pyrolysis -- Chemical Coprecipitation for Hydrophobic and Hydrophilic Magnetite Nanoparticles -- Magnetic Microgels: Synthesis and Characterization -- Vesicles and Composite Particles by Rotating Membrane Pore Extrusion -- Synthesis of Functionalized Magnetic Beads Using Spray Drying -- Industrial Production, Surface Modification and Application of Magnetic Particles -- Part II: Magnetic Separation Devices -- Magneticall Enhanced Centrifugation for Industrial Use -- Design and Performance of a Pilot Scale High-Gradient Magnetic Filter using a Mandhala Magnet and its Application for Soy-Whey Protein Purification -- Continuous Magnetic Extraction for Protein Purification -- Part III: Process examples -- In-situ Magnetic Separation of Pilot Scale : A Tool for Process Optimization -- An Industrial Approach to High-Gradient Magnetic Filtration in the Food Industry -- Conclusion.
Keywords: Chemistry; Biotechnology; Food -- Biotechnology; Biomaterials; Chemistry; Biotechnology; Biomaterials; Food Science; Electronic books